Sugarcane Bagasse Reinforced Polyester Composites: Effects of Fiber Surface Treatment And Fiber Loading on The Tensile And Flexural Properties. Issue 1 (October 2020) - Zakaria, Muhammad Salihin; Musa, Luqman; Nordin, Razif Muhammed; Halim, Khairul Anwar Abdul
Abstract: The effect of fiber surface treatment and fiber loading on the tensile and flexural properties of untreated and treated fiber-based sugarcane bagasse reinforced polyester (SBRP) composites have been investigated. Sugarcane bagasse fibers were alkalized with 1, 3 and 5% concentration of sodium hydroxide (NaOH) solution combined with different fiber loading formulation 0, 20, 30 and 40 php, and hot-pressed to form natural fibers composite were prepared. The results indicated that the incorporation of bagasse fiber composites alkalized with 3% NaOH solution improved the tensile strength and modulus of reinforced composites meanwhile the untreated bagasse gave the lowest value. However, the elongation at break (Eb) indicated that treated bagasse fiber composites show a lower value compared to untreated composites. A similar trend also obtained for flexural strength and modulus.